2019
DOI: 10.1111/cns.13273
|View full text |Cite
|
Sign up to set email alerts
|

microRNA cluster MC‐let‐7a‐1~let‐7d promotes autophagy and apoptosis of glioma cells by down‐regulating STAT3

Abstract: Background Accumulating evidence has highlighted the correlation between microRNAs (miRNAs) and the progression of glioma. However, the role of miR cluster MC‐let‐7a‐1 ~ let‐7d in glioma remains elusive. Thus, the current study aimed to investigate the effect of miR cluster MC‐let‐7a‐1 ~ let‐7d on glioma progression. Methods and Results Microarray data analysis provided data indicating the involvement of miR cluster MC‐let‐7a‐1 ~ let‐7d in glioma via STAT3. The expression of let‐7a‐1, let‐7d, let‐7f‐1, and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Epigenetic factors such as DNA methylation, histone acetylation, and miRNAs are all reflections of changes in environmental stimuli 40,41 . MiRNA, a small RNA sequence, can play a major role in cell differentiation, biological development, and disease development by directly inhibiting target gene translation 42,43 . Recent years, there were literatures reported the roles of miRNAs in a variety of pregnancy‐related complications such as preeclampsia and FGR, indicating its importance in pregnancy 44,45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic factors such as DNA methylation, histone acetylation, and miRNAs are all reflections of changes in environmental stimuli 40,41 . MiRNA, a small RNA sequence, can play a major role in cell differentiation, biological development, and disease development by directly inhibiting target gene translation 42,43 . Recent years, there were literatures reported the roles of miRNAs in a variety of pregnancy‐related complications such as preeclampsia and FGR, indicating its importance in pregnancy 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…40,41 MiRNA, a small RNA sequence, can play a major role in cell differentiation, biological development, and disease development by directly inhibiting target gene translation. 42,43 Recent years, there were literatures reported the roles of miRNAs in a variety of pregnancy-related complications such as preeclampsia and FGR, indicating its importance in pregnancy. 44,45 In general, DNA methylation and histone acetylation are believed to regulate gene expression at mRNA levels while miRNAs are believed to regulate gene expression both at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study confirmed that STAT3 was the direct target gene of these three let-7 miRNA dual luciferase reporters. Then, cell fluorescence staining and experiments in mouse models confirmed that miRNA clusters of let-7a-1 ~ let-7d acted as tumour suppressors in glioma [ 40 ]. In terms of migration and invasion, the growth and metastasis of GBM depend on the expression of matrix metalloproteinase 2 (MMP2).…”
Section: Mirnas Involved In the Stat3 Signalling Pathwaymentioning
confidence: 99%
“…Let-7 family miRNAs are involved in multiple pathways contributing to cell survival and cell death and influence cancer risk and prognosis as well as neuroinflammation [153][154][155]. It was shown recently, that miR cluster MC-let-7a-1~let-7d promotes glioma cell autophagy and apoptosis by repressing signal transducer and activator of transcription 3 (STAT3) [156].…”
Section: The Most Promising Potential Circulating Mirna Biomarkers Anmentioning
confidence: 99%